Chemical oceanography - Millero, Frank J. (CRC/Taylor and Francis, 2006)
Chemical Oceanography, Third Edition, is a survey of essential concepts that contains a wealth of new data and maps, resulting in a more in-depth examination of oceanic biogeochemical processes. The most up-to-date compilation of essential concepts and data available on the subject, this book responds to the need for a thorough, yet straightforward approach to the subject for students, researchers, and other professionals in marine science, geochemistry, and environmental chemistry. The third edition of Chemical Oceanography incorporates significant findings on the properties of oceans from recent, large-scale oceanographic programs and valuable new data derived from additional experiments. It also discusses the interactions of metals with inorganic and natural organic ligands and the effect of speciation of metals on bioavailability and toxicity. The section on carbonate systems now examines the input of fossil fuel CO2 into the ocean and its effect on the pH of the world oceans.